Sovereign debt and the financial crisis : will this time be different? - Braga, Carlos Alberto Primo; Vincelette, Gallina Andronova (Washington, D.C. : World Bank, 2011)
The book presents, in an integrated approach, drawing on theoretical policy-relevant research and evidences from practitioners' experiences in developing, emerging market, and developed economies, on the current debt challenges facing countries around the globe.
Includes bibliographical references and index.
oif 22/05/13
Loan
Keywords: Debts, Public; Financial crises; Economic policy; Monetary policy; Debt relief